2015
DOI: 10.1016/j.jvs.2015.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistula outcomes in the elderly

Abstract: This meta-analysis confirms that adequate 12-month primary and secondary AVF patency rates can be achieved in elderly patients. Brachiocephalic AVFs have both superior primary and secondary patency rates at 12 months compared with radiocephalic AVFs. These important data can inform clinicians' and patients' decision-making about suitability of attempting AVF formation in older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
1
37
2
Order By: Relevance
“…In comparison with previous studies (Lok) and metaanalyses (McGrogan), primary and secondary patency rates were lower the first year versus the second year (36.7% versus 53.6%, 56.8% versus 71.6%) [21,28]. Rates of failure to mature were higher in the first year as well, at 61.8% versus 49% [21].…”
Section: Vascular Accesscontrasting
confidence: 56%
“…In comparison with previous studies (Lok) and metaanalyses (McGrogan), primary and secondary patency rates were lower the first year versus the second year (36.7% versus 53.6%, 56.8% versus 71.6%) [21,28]. Rates of failure to mature were higher in the first year as well, at 61.8% versus 49% [21].…”
Section: Vascular Accesscontrasting
confidence: 56%
“…Over 90% of the endoAVFs in NEAT reached physiologic maturation and 67% of endoAVFs were routinely used for dialysis with 2-needle cannulation. The endoAVF usability of 67% compares with the 40%-70% rates reported in the surgical AVF literature (9,20). The lower rate of procedures to facilitate maturation, such as the use of angioplasty, stenting, and thrombectomy, reflected the low complication and early thrombosis rate seen in NEAT and the high physiologic endoAVF maturation observed (11).…”
Section: Discussionmentioning
confidence: 93%
“…18 However, other studies have suggested that age does not have an important impact on fistula outcomes. 19-22 In a retrospective study of 658 patients referred for fistula creation, Weale et al 22 assessed the impact of age on functional outcomes and found no difference in primary or secondary patency with radiocephalic and brachiocephalic fistulas in patients less than 65 years of age, 65 to 69 years of age, and those 80 years of age and older. Inconsistency in prior studies may relate to sample size considerations, a preponderance of single-center studies, differences in definitions, and the lack of adequate risk adjustment for other important predictors of fistula outcomes.…”
Section: Discussionmentioning
confidence: 99%